Peningkatan Budaya Tulis Melalui Koran Ibu - Ikka Kartika; Ahmad Yani; Abdul Holik (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2011)
A new literate person is a member of the newly literate society, is considered problematic if it is less or or unable to use and improve their new abilities. The reason is, they could be re-illiterate so that it replenishes the long list of illiterate population in Indonesia which has no end. Getting over this problem, The Ministry of National Education, Directorate General of PNFI, Directorate of Public Education, launched “Improving Culture of Writing Through Newspapers ‘Ibu“ program. When it applied it was turning out to the increase of writing habit among some new literate persons. The impact, it reduced the number of illiterate population. For optimal results, several contributing factors are considered, they are: the moral support of the local government, the existence of a tutor, the character of  participants,  giving participants a chance to  spread  ideas or their  writings on  newspaper. Obstacles can be solved  by growing a conditions and flexible learning situation, conducive and comfortable for all sides.